Movie viewership in Singapore. - Liew, Janet. (2008)
The number of cinemas in Singapore has increased tremendously in the 1990s, notably after the entry of Golden Village. Other players like United Artists and Studio City have also found their way here soon after. The emergence of suburban shopping centres has been a stepping stone to the expansion plans of the cinema operators as cinemas are now one of the anchor tenants there. This project traces how the cinema industry developed into the multi-dollar industry it is today.